Intensi Berwirausaha Pada Pelajar Kelas Ekstrakurikuler Kewirausahaan SMAK St. Louis 1 Di Surabaya [The Entrepreneurship Intentions of Entrepreneurship Students in Extracurricular Classes at SMAK St. Louis 1 in Surabaya] - Gregorius Romaryo Tanubun; Maichal Maichal (Universitas Pelita Harapan, 2016)
The purpose of this research is to understand: (1) the influence of family on entrepreneur intention; (2) the impact of entrepreneurial study on entrepreneur intention; and (3) the difference in entrepreneurial intention among an entrepreneurial class of students at SMAK St. Louis 1 in Surabaya. The population of this research is students of an entrepreneurial class at SMAK St. Louis 1 in Surabaya. The sampling technique used is census with 40 respondents as samples. This research is a quantitative research with multiple regression method and independent samples t-test with SPSS 23 as analysis tool. The findings of this research indicate that: (1) family variable (K) reacts significantly negative towards entrepreneurial intention (IB), (2) entrepreneurial education variable (PK) reacts significantly towards entrepreneurial intention (IB), and (3) no difference is found between men and women.